Modulation of the Antioxidant System of Caco-2 Cells in the Presence of Aflatoxin B1, Ochratoxin A, and Ferulic Acid - Andreea-Luminița Rădulescu; Roua Gabriela Popescu; Mihaela Balas; George Cătălin Marinescu; Anca Dinischiotu (Toxins, 2025)
Food security and food safety are major aspects for human and animal health, yet mycotoxins contaminate 60–80% of food crops before and after harvest, elevating the risk of chronic toxicity and cancer development. This study investigates the potential of ferulic acid (FA) as an antioxidant against mycotoxin-induced oxidative stress in Caco-2 cells exposed to aflatoxin B1 (AFB1) and ochratoxin A (OTA) for 24 and 48 h. The effects on the degree of lipid peroxidation and non-enzymatic and enzymatic mechanisms against oxidative stress were evaluated. FA appears to mitigate oxidative stress by modulating lipid and protein oxidation, decreasing the level of 4-hydroxy-2-nonenal (4-HNE), increasing superoxide dismutase (SOD) activity, and preserving thiol groups by scavenging reactive oxygen species (ROS). Additionally, the reduction in polyubiquitinated Nrf2 level, and higher SOD activity, suggest that FA stabilizes Nrf2, delaying its degradation and reinforcing its antioxidant role. These findings indicate that FA partially counteracts mycotoxin-induced oxidative damage, highlighting the need for further investigation into its long-term effects.